Academic library paraprofessionals' role and job satisfaction - Gonda, Jojie A.; Faderon, Rosalie B.; Santos, Herminia H. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2006)
Library paraprofessionals are considered potential professional librarians, they should be given opportunities to grow and have a career path to improve their craft. The study examined the role and job satisfaction of academic library paraprofessionals in selected academic university in Metro Manila.
The survey questionnaire was the basic tool used. The respondents of the study were 105 library paraprofessionals. The data that were gathered were tabulated, tallied, analyzed and interpreted using frequency distribution, percentages and mean ranking to carry out the objectives of the study. Descriptive statistics such as frequency mean and percentage were used to present the data as well as the general trend of the perception under each item that were included in the questionnaire.
The study found that the majority of the respondents are males in contrast with other studies that most of the library workers are female. Most of the respondents are married, and college graduates, they receive better compensation compared to public libraries and they have permanent status. Most of the respondents work in the service area and worked more than 15 years. Personally applied for the position and through recommendation ranked first in how they applied in their position. Majority of them attended trainings/seminars/workshops. Library work is challenging is the main reason why they work in the library. Their special skills and abilities are human relationship followed by computer/typing skills. Results of the survey revealed that they are motivated by their work. Salary is the biggest motivating factor that made the paraprofessionals satisfied with their job at present. Paraprofessionals both in the public and academic libraries unanimously agreed that they need training as part of their continuing professional education.
Vita.
Special Problem (Master of Library and Information Science)--University of the Philippines Diliman
Keywords: Library technicians -- Philippines -- Manila Metropolitan Area; Academic libraries -- Philippines -- Manila Metropolitan Area -- Employees; Library employees -- Philippines -- Manila Metropolitan Area